The Role of Visual Communication During Covid Pandemic 19 - Mohd Tahir, Hanafi; Baharom, Shahrel Nizar; Abd Rashid, Mohd Shahril (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020), 2020)
The process of progress and development of communication has begun over the centuries and through various phases of development over time according to the passage of time. Various methods have been developed to facilitate communication activities. The excitement and fun of communicating activities takes place as if there is no time limit. Communication is an important aspect to meet the needs of daily life. There are no terms rest, pause or ‘sleep’ for communication. Keywords: Communication Development, Daily Needs